Development of Two Pommel Mushrooms for Men's Artistic Gymnastics - Darmawan, Agus (Journal of Physical Education Health and Sport, 2020)
The purpose of this research was to see if the two-saddle mold device could be used asa means of training an athlete in overcoming the difficulty of mastering a sirkel movement on the saddle. The study method used samples as many as 16 athletes, 2 gymnasts and 2 equipment experts. Research came up with the prototype two-saddle fungus. Gymnasts claim that 90% of saddle mushroom instruments can be used as a training tool, equipment experts claim that mushrooms are safe for athlete training, and as many as 16 claim that moldings can be used for circular motion exercises. The conclusion can be drawn that an athlete's two-saddle mushroom instrument was effectively constructed for the training of sirkel movements using a saddle horse as well as for the limitations of both the means and the gymnast equipment in central Java.